Rethinking counselling in prenatal screening: An ethical analysis of informed consent in the context of non-invasive prenatal testing (NIPT) - Kater‐Kuipers, Adriana (Bioethics, 2020)
Informed consent is a key condition for prenatal screening programmes to reach their aim of promoting reproductive autonomy. Reaching this aim is currently being challenged with the introduction of non-invasive prenatal testing (NIPT) in first-trimester prenatal screening programmes: amongst others its procedural ease—it only requires a blood draw and reaches high levels of reliability—might hinder women’s understanding that they should make a personal, informed decision about screening. We offer arguments for a renewed recognition and use of informed consent compared to informed choice, and for a focus on value-consistent choices and personalized informational preferences. We argue for a three-step counselling model in which three decision moments are distinguished and differently addressed: (1) professionals explore women’s values concerning whether and why they wish to know whether their baby has a genetic disorder; (2) women receive layered medical-technical information and are asked to make a decision about screening; (3) during post-test counselling, women are supported in decision-making about the continuation or termination of their pregnancy. This model might also be applicable in other fields of genetic (pre-test) counselling, where techniques for expanding genome analysis and burdensome test-outcomes challenge counselling of patients.